ANAKBAYAN and public opinion towards basic social services. - Rojas, Angelica T.
Every SMO has its own methods in communicating its advocacy to the public. These methods help in shaping public opinions towards a certain issue. The problem then, is how does SMOs shape public opinion? The research paper will look into these methods and the kind of opinions being generated. In order to answer the research problem, the study has conducted three (3) methodologies, namely, in-depth interview, content analysis and survey. Based on the methodologies, the paper has presented the two methods in shaping the public opinion, the direct and indirect methods. The use of direct method means the use of face-to-face interaction in communicating their advocacy to the public. The use of indirect method, on the other hand, is the use of media both the old and new to advance the organization?s advocacy to the people. The important implication generated from the paper is that the kind of methods employed by the SMO will be useless if it could not be received by the target community or audience. The SMOs should make sure that their target community or audience are able to access and participate in the methods they employ.